IMPLEMENTASI KEBIJAKAN BADAN PENGAWAS OBAT DAN MAKANAN TERHADAP IZIN EDAR OBAT TRADISIONAL DAN KOSMETIK DI PEKANBARU TAHUN 2018 - Septian Barizky; Khairul Anwar (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
It is explained to business actors that pharmaceutical and food preparations without a distribution permit and food contain hazardous materials that pose a risk to health, and offenders may be subject to criminal sanctions in accordance with Law Number 36 of 2009 concerning Health and Law Number 18 of 2012 concerning Food. Criminal acts that have been determined in the field of pharmaceutical supplies in the form of cosmetics that do not have a distribution permit are applied to the elements of Article 197 of the Law of the Republic of Indonesia Number 36 of 2009 concerning Health. This thesis discusses how the implementation of supervision carried out by the Food and Drug Supervisory Agency in Pekanbaru as a non-ministerial government authorized to conduct inspections and supervision of the circulation of cosmetic products in Pekanbaru City, especially cosmetics that are not in accordance with distribution permits and do not have certification from BPOM. To explain with this supervision, consumers can be more alert and can be protected. This research uses a descriptive format of research that aims to explain, summarize various conditions, situations, or various variables that arise in the community that is the object of this research based on what happened. Researchers also conducted research directly into the field by interviewing related parties, namely the Center for Drug and Food Control of the Republic of Indonesia, the Food and Drug Supervisory Agency in Pekanbaru. The results of the study show that there are still many cosmetic products that do not meet the standards or do not have a distribution permit in the market. As well as the implementation of supervision before being circulated as a preventive measure to ensure that drugs and food in circulation meet the standards and requirements for safety, efficacy/benefits and product quality. Keywords: Implementation, Supervision, BPOM, Cosmetic Distribution Permit